Otimização dimensional do eixo metroferroviário tipo D a partir dos métodos de otimização do Ansys Workbench - Neves, Douglas Mayor (2022)
Software are essential tools for the development of engineering activities, allowing advances and optimization of processes and machines in the industrial scope, as well as in the academic fields. With the advancement of computers, access to advanced programs and computational methods are now a reality, as well as the use of academic versions that leverage scientific research, allowing the use of day-to-day machines to carry out analyzes and develop high complexity projects within the most diverse areas of engineering. Mechanical failures are a major cause of accidents in the field of cargo transport and in many others. Mechanical failures can be caused by several factors, among them it is possible to mention static failures, which do not vary over time, but when they exceed the yield stress of the material, they cause plastic or permanent deformation. On the other hand, dynamic failures are failures due to repetitive or cyclical efforts, which allow the material, after a certain number of repetitions, to reach fatigue. With this, the present work aims, with the use of the ANSYS software and with the concepts and studies developed during the graduation, to carry out the structural optimization of the railway axles to minimize the mass, aiming at the determination of the geometric parameters of the roll axis, meeting the restrictions or minimum requirements pre-established by the standard and imposed on the modeling. This work is also responsible for verifying and comparing the results based on solid mechanics concepts and analytical expressions to validate the simulations.